Do county financial marketization reforms promote food total factor productivity growth?: a mechanistic analysis of the factors quality of land, labor, and capital - Liu, Yang; Cui, JunFu; Jiang, Hui; Yan, Hua (Frontiers in Sustainable Food Systems, 2023)
Giving full play to the role of financial credit in supporting the total factor productivity of food is of great significance in guaranteeing food security and promoting sustainable agricultural development. However, due to the low profit and high-risk nature of China's food cultivation industry, and the profit-tending and risk-averse nature of financial capital, can the county financial marketization reform become a driving force for food total factor productivity growth? And what is the role of factor quality of land, labor and capital in the relationship? It is not yet known. Using panel data for 729 counties in China from 2010 to 2019, this paper analyzes the impact of county financial marketization reforms on food total factor productivity, focusing on the role of factor quality mechanisms such as land, labor, and capital. The findings demonstrated that county financial marketization reforms promoted food total factor productivity growth by fostering technical advancement, while technical efficiency did not play a significant role. Heterogeneity analysis shows that the effect of county financial marketization reform on total factor productivity of grain is not significantly different in eastern and central China. There is a significant difference in the western region, where the financial market reform in counties has inhibited the growth of grain total factor productivity. In terms of different functional areas of grain production, the facilitating effect is only played in the main grain production area, not significant in the grain production and marketing balance area. Moreover, the inhibiting effect is played in the main grain marketing area. Mechanistic analysis finds that county financial marketization reforms promoted food total factor productivity growth by improving labor quality and land quality, while agricultural capital quality has a masking effect. On this basis, it is necessary for the government to implement differentiated financial market-oriented reform strategies and to guide and encourage county financial institutions to provide financial services to improve the quality of agricultural labor and farmland through tax incentives and loan interest subsidies.